Islam dan Modernitas dalam Pandangan Fethullah Gulen - Sehat Ihsan Shadiqin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Phobia and prejudice toward Islam in America and Europe are contributed  by a small particular group that name their violence and movement on behalf of  Islam. In fact, Islam is a religion that calls for peace and harmony. But these  impressions are still inadequate to purify the image of Islam. It requires to  systematic effort to show that the truth teaching of Islam that guarantees and supports the universal values of mankind to life in peace and harmony. Fethullah  Gulen, who is scholar, a preacher, a sufi, a teacher and is a Muslim activist from  Turkey, is one of scholars and actors how has done this mission. Currently, Gulen  has tens million followers from around the world that bring about to become one  of the most influential person in contemporary Muslim world. This papers seeks  to see the basic and model of religious social movement that are done by  Fethullah Gulen in his campaign in cosmopolitan society. The campaign strongly  states that Islam is very relevant to modern life. The papers specifically answers  three fundamental questions; how does Gulen interpret scare texts of Islamic  teaching? What model of interpretation that Gulen employs in understanding  various dimensions of Islamic Teaching? How the normative concepts of  Fethulllah Gulen’s Teaching used to spread Islamic teaching